Leucine supplementation has no further effect on training-induced muscle adaptations - Thomazi De Andrade, I.; Gualano, B.; Hevia-LarraÍn, V.; Neves-Junior, J.; Cajueiro, M.; Jardim, F.; Leite Gomes, R.; Artioli, G. G.; Phillips, S. M.; Campos-Ferraz, P.; Roschel, H. (Medicine & Science in Sports & Exercise, 2020)
Introduction: Several acute studies have suggested that leucine is a key amino acid to drive muscle protein synthesis. However, there are very few studies on the long-term effects of leucine supplementation on resistance training (RT)-induced gains in muscle mass and strength. We sought to determine the impact of 10 g of leucine on muscle mass and strength in response to RT in healthy young men. Methods: Twenty-five, resistance-trained men (27 ± 5 yr; 78.4 ± 11.6 kg; 24.8 ± 3.0 kg·m-2) consuming 1.8 ± 0.4 g protein·kg-1·d-1, were randomly assigned to receive 2 × 5 g·d-1 supplementation of either free leucine (LEU n = 12) or alanine (PLA n = 13) while undergoing a supervised 12-wk, twice-weekly lower-limb RT program. One-repetition maximum (leg-press 1RM) and muscle cross-sectional area (mCSA) of the vastus lateralis were determined before (PRE) and after (POST) the intervention. Additionally, three 24-h dietary recalls were also performed at PRE and POST. Results: Protein intake was roughly double that of the RDA in both groups and remained unchanged across time with no differences detected between groups. Similar increases were observed between groups in leg-press 1RM (LEU, 19.0% ± 9.4% and PLA, 21.0% ± 10.4%, P = 0.31) and mCSA (LEU, 8.0% ± 5.6% and PLA, 8.4% ± 5.1%, P = 0.77). Conclusions: High-dose leucine supplementation did not enhance gains in muscle strength and mass after a 12-wk RT program in young resistance-trained males consuming adequate amounts of dietary protein.